2018
DOI: 10.1088/0256-307x/35/5/058101
|View full text |Cite
|
Sign up to set email alerts
|

Growth ofβ-Ga2O3Films on Sapphire by Hydride Vapor Phase Epitaxy

Abstract: Two-inch Ga2O3 films with ( 201)-orientation are grown on 𝑐-sapphire at 850-1050 ∘ C by hydride vapor phase epitaxy. High-resolution x-ray diffraction shows that pure 𝛽-Ga2O3 with a smooth surface has a higher crystal quality, and the Raman spectra reveal a very small residual strain in 𝛽-Ga2O3 grown by hydride vapor phase epitaxy compared with bulk single crystal. The optical transmittance is higher than 80% in the visible and near-UV regions, and the optical bandgap energy is calculated to be 4.9 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Besides the diffraction peaks of sapphire, the reflections corresponding to the {2̄01} and {3̄10} planes family of β-Ga 2 O 3 are observed, which is different from our previous report of single (2̄01)-oriented films obtained on the (0001) sapphire substrate. 23 The appearance of unusual {3̄10} diffraction peak would result from the specific growth systems and conditions. The relative intensity ratio I (3̄10) / I (2̄01) is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the diffraction peaks of sapphire, the reflections corresponding to the {2̄01} and {3̄10} planes family of β-Ga 2 O 3 are observed, which is different from our previous report of single (2̄01)-oriented films obtained on the (0001) sapphire substrate. 23 The appearance of unusual {3̄10} diffraction peak would result from the specific growth systems and conditions. The relative intensity ratio I (3̄10) / I (2̄01) is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, β-Ga 2 O 3 films were grown on sapphire substrates in a vertical home-made HVPE system with a two-zone furnace at atmospheric pressure. 23 Prior to deposition, sapphire substrates were ultrasonically cleaned in acetone and alcohol, rinsed in deionized water, and then dried in N 2 . During the growth process, HCl gas reacted with liquid Ga to synthesize GaCl in the first zone at 900 °C, and then GaCl gases were transported into the growth zone and reacted with O 2 to form β-Ga 2 O 3 films on sapphire substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vapor phase epitaxy is a commercially promising technique for mass production of β -Ga 2 O 3 . Based on VPE, the halide vapor phase epitaxy (HVPE) method enables a growth rate as high as 250 μm/h [ 55 ] and the wafer size from 2 to 6 inches [ 56 ], it is thus a suitable technique for thick films with high purity for high voltage vertical switching devices. Furthermore, with the presence of chlorine catalyst in the growth chamber, this technique exhibits the growth of metastable phases of Ga 2 O 3 , such as α and ε [ 57 ].…”
Section: Gallium Oxide (Ga 2 O 3 )mentioning
confidence: 99%
“…Furthermore, with the presence of chlorine catalyst in the growth chamber, this technique exhibits the growth of metastable phases of Ga 2 O 3 , such as α and ε [ 57 ]. The HVPE method suffers from a high level of roughness on the surface even at a relatively low growth rate [ 56 , 58 ]; an electrical mechanical [ 59 ] or a chemical mechanical [ 60 ] polishing can be employed to remove further deep surface pits formed during the growth. Leach et al [ 61 ] reported a vast difference in surface morphology and XRD full-width half-maximum (FWMH), between sufficiently and insufficiently CMP polished (discriminated by the polishing times of the various polishing steps) β -Ga 2 O 3 wafers grown by HVPE.…”
Section: Gallium Oxide (Ga 2 O 3 )mentioning
confidence: 99%